Influence of graphite nodules on fatigue limit of nodular cast iron - Costa,N. (2008)
This paper describes the fatigue behaviour of a nodular cast iron dispersed within martensitic matrix microstructure. Cyclic fatigue tests have been performed on nodular cast irons. The effects of both the microstructure and the graphite nodules geometrical features such as shape and size, on the fatigue behaviour of nodular cast iron were studied. The rule of size and position of graphite nodules on the fatigue limit has been established. On this study is verified if the (square root of the maximum graphite nodule area projected onto the principal stress plane) parameter model proposed by Murakami, quantitatively predicts with accuracy the fatigue life of the nodular cast iron. In this paper, a high strength nodular cast iron, with rupture strength of about 1.300 MPa and Young modulus of about 165 GPa has been used. Comparison between experimental results and parameter model has been assessed.